Locally Advanced Breast Cancer in Pakistani Women: Clinical Features and Prognostic Factors: Breast Cancer Prognostic Features - Khan, Ramsha; Hashmi, Fazila; Masroor Bhatti , Aisha; Iqbal Memon, Amir; Iqra, .; Nayab, . (Pakistan Journal of Health Sciences, 2023)
locally advanced breast cancer poses a significant health challenge due to delayed diagnosis and limited access to healthcare resources among Pakistani women. Understanding the clinical features and prognostic factors specific to Pakistani women can help healthcare professionals identify high-risk patients, initiate timely interventions, and improve survival rates. Objective: To investigate the clinical features and prognostic factors associated with locally advanced breast cancer (LABC) in Pakistani women. Methods: The study was carried out at the Department of Surgery, Liaquat University of Medical & Health Sciences, Jamshoro. 300 patients with LABC had their data gathered. Age and socioeconomic status were recorded under the category of demographics. Clinical information included the date of presentation, family history of breast cancer, the lump that was the presenting symptom, the ulceration, and other skin changes. Tumour size, histopathology, Bloom & Richardson grading, estrogen receptor (ER), progesterone receptor (PR), and HER2 status are histopathological factors. Results: The study showed that 30% of LABC patients who received standard Tri modality treatment died within two years. Only 25% of patients were found to have more than two years of disease-free survival. On the other hand, 70% of patients survived with eventful (recurrence/metastases) survival. Conclusions: Though there is a substantial mortality rate within one year, a significant proportion of patients survive beyond one year. Disease recurrence or metastases are prevalent as per the current study, emphasizing the need for comprehensive follow-up and targeted therapies to improve long-term outcomes.